The policy in handling transnational crime at Indonesia’s Maritime Borders (Study at tanjung Balai Asahan, North Sumatera Province) - Puguh, Adi Satriyo; Surryanto, Djoko Waluyo; Afifuddin, Moch.; Samudro, Eko G. (Technium Social Sciences Journal, 2022)
The strategic geographical constellation on the one hand, can bring benefits to Indonesia, but on the other hand, this position is very vulnerable to threats, both military threats from foreign countries and non-military threats in the form of crimes or illegal activities. Meanwhile, accelerated globalization with technological advances, especially information technology, makes it seem as if there are no boundaries between countries. The rise of transnational crimes in Indonesia, of course, has implications for national defense. Therefore, a comprehensive and integrated effort is needed to minimize the occurrence of transnational crimes at Indonesia’s maritime borders, especially in Tanjung Balai Asahan, Medan, North Sumatra Province. It is proven by the increasing trend in the number of transnational crime rates that continue to increase from year to year and it is made worse by the involvement of the community and unscrupulous security forces that choose shortcuts to seek profit by carrying out these illegal actions as happened in several research taken. From the results of the analysis, it was found that 4 types of crime dominate in the Tanjung Balai area, they are smuggling of illegal goods, Drugs, Human trafficking, and People smuggling. Moreover, the weaknesses that made the crimes happened can be categorized as the lack in communication, resources, disposition, and Bureaucratic structure.